Extraction, Memorialization, and Public Space in Leo McKay’s Albion Mines - Thompson, Peter (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (The University of New Brunswick, 2012)
In Anne of Tim Hortons (2011), Herb Wyile argues that Leo McKay’s novel Twenty-Six (2003) situates the 1992 Westray coal mining disaster in a broad set of economic and social conditions affecting Atlantic Canada at the end of the twentieth century. This essay considers McKay’s novel in the context of a wider debate over public space in northern Nova Scotia’s Pictou County through post-industrial critiques from Tim Edensor, Rebecca Scott, and Stephen High and David Lewis. While the state’s memorial infrastructure privileges straightforward narratives about the bravery and sacrifice of the miners who were killed in Westray and other disasters, and presents a smooth transition between the dangerous and violent industrial era and the clean and efficient post-industrial era, Twenty-Six employs a nonlinear timeline and images of abandoned space to contest this progressive image of the region.